Rhythm Responses of Preschool and First and Second-Grade Elementary School Children in Different Tasks of Duplicating Rhythmical Patterns - Maja S. Sokolović Ignjačević; Gabrijela B. Grujić; Jelena D. Stanivuković (University of Belgrade, Teacher Education Faculty, 2023)
Enrolment exam for music schools is an important moment when a child potentially, in parallel with attending general education, starts attending specialized, music education. In this paper we are questioning the existing concept of evaluating rhythmic abilities within the entrance exam for music schools. This evaluation currently includes duplicating rhythmical patterns, performed through one of two tasks: first one involves clapping the beat while performing the rhythmical patterns vocally, using the neutral syllable and the second one includes duplicating rhythmical patterns only through clapping. Nevertheless, in pedagogical practice the choice between the two tasks is usually arbitrary, since it is assumed that the results on both types of tasks would be similar. Furthermore, the level of difficulty of the given patterns within the test is arbitrary, since the teachers are usually inventing them "in situ" for each child. All respondents are evaluated in the same way, regardless of their age (which usually varies from 6 to 8). The aim of this paper is to contribute to the potential improvement of the quality and fairness of the enrolment exam for all participants, through investigation of the possible differences in the results of the same participants on two types of tests and comparing the results between the tasks with different level of difficulty, between the three age groups of children and between the two genders. The research was carried out within both - elementary school and preschool facilities in Belgrade and the sample consisted of 278 children. The results revealed that participants were more successful in the first type of task. Statistically significant differences were found between participants of different gender in their achievement in favour of girls and also between participants of different age groups, in favour of the second graders. Pedagogical implications were defined, regarding (1) transformation of traditional testing procedures regarding evaluating children's rhythmical abilities within enrolment exams in Serbian music schools, as а base for optimal selection of children and indirectly, optimal results of the teaching process in music schools and (2) the content of teaching and activities in elementary schools and preschools in the field of rhythm.